PENGARUH MODEL PEMBELAJARAN FLIPPED BERBANTUAN GOOGLE CLASSROOM TERHADAP HASIL BELAJAR SISWA PADA MATERI HUKUM DASAR KIMIA - Kasik, Olivia Clara; Masruhim, Muh. Amir; Erika, Farah (PROSIDING SEMINAR KIMIA, 2025)
Students' lack of activity in participating in chemistry learning due to learning models that are used too often and lack of variety by teachers causes students to feel bored during learning, resulting in low student learning outcomes. The type of research used was quantitative experimental research, namely quasi-experimental design. Samples were taken by purposive sampling consisting of class X-4 (experimental class) and class X-2 (control class), with a total of 72 students. Data collection techniques use observation, documentation and tests. The data was analyzed using a parametric test, namely the independent sample t-test showing a sig value. 0.00 < 0.05, then HO is rejected and Ha is accepted. This means that there is an influence of the flipped learning model assisted by Google Classroom on student learning outcomes in basic chemical law material. Keywords : Flipped Classroom, Google Classroom, student learning outcomes